DETERMINATION OF THORACIC FLUID CONTENT IN PATIENTS WITH PULMONARY CONTUSION BY ELECTRICAL CHEST IMPEDANCE DETERMINATION AND BY ANTHROPOMETRY - Kursov , Serhii (Collection of scientific papers «ΛΌГOΣ», 2023)
Background. Pulmonary pathology of various origins accompanied very often by the accumulation of free fluid in the body. The most common mechanism is an inflammatory reaction and hypoxemia, due to which there is a pathological increase in vascular permeability with subsequent movement of fluid to the interstitial sector of extracellular water compartment. These mechanisms are also common in pulmonary contusion accompanying blunt chest injuries. Currently, in foreign scientific publications, one can observe a significant increase in interest in objectifying the amount of fluid in the chest by determining changes in its electrical impedance, thanks to which the Thoracic Fluid Content (TFC) indicator is calculated [1]. The purpose of study was to determine the amount of fluid in the chest in patients with blunt thoracic trauma and pulmonary contusion.